Culture Representation Through Visual Images in The Korean Foundation Level 1 Textbook: A Multimodal Analysis - Handayani, Nur Wulan; Triarisanti, Risa; Lubis, Arif Husein (Universitas Negeri Makassar, 2024)
Abstract. This study aims to investigate culture representation through visual images in a Korean as a foreign language textbook for Indonesian students. It specifically exhibits how cultures are represented through visual images and how they are implicated to KFL learning. Culture and language are closely related, and understanding the cultural values underlying the target language can greatly affect the effectiveness of the learning process. Even though this topic has been the subject of substantial prior research, many have not been explored in the context of Korean textbooks as learning foreign languages. The method used in this study was qualitative using a multimodal discourse analysis. The data were analyzed using the image representation mode of Kress van Leeuwen (KvL). The data were collected from visual images showing cultural identities such as gender roles and ideology, contained in each chapter of the Korea Foundation Level 1 textbook, focused on the speaking (Malhagi) and cultural sections. The results of the data analysis show that cultural representation is dominated by Korean culture in both animated and non-animated images. However, the social role of people's lives represented in the picture corresponds to Indonesia and some pictures are found to be relevant to Indonesia, as the religion of the majority of Indonesians is depicted in the book. Almost all images are illustrated with animated visuals. Male gender is more heavily highlighted than female gender, rendering gender bias. This is related to the Confucian principles that exist in South Korea. Apart from the ulterior motives, the existence of Korean language learning textbooks for Indonesians provides benefits as a multimodal learning medium and helps teachers and students as a support medium for teaching and learning purposes. Keywords: Visual Language, Representation Mode, Multimodal Discourse, Culture